Effect of Information Technology and Product Quality on Competitive Advantage in the Chemical Industry - Syahchari, Dicky Hida; Saroso, Hardijanto; Lasmy, Lasmy; Sudrajat, Darjat; Herlina, Maria Grace (ExcelingTech, 2020)
The purpose of this study is to analyze the impact of information technology and product quality on competitive advantage in chemical companies in Indonesia. Today, the competitive advantage in the chemical industry has become the principal capital for companies to compete in the global market. Based on previous studies, the authors seldom find research investigating the relationship between information technology and overall product quality with a competitive advantage, especially in the context of chemical companies in Indonesia. That basis is the novelty of this research. This research uses quantitative methods with a sample of 114 chemical companies in Indonesia. The sampling technique uses an intentional random sampling method, and the data analysis uses multiple regression analysis with SPPS 25. The results of this study are information technology, and the quality of the product has a significant positive relationship with the advantage of competitive. This research implies that companies must be able to innovate to continue developing the quality of existing products while maintaining a good strategy in business development. To be able to continue competing in the global market and satisfy the needs of customers. The use of information technology in companies must be more developed to increase competitive advantage.Keywords— Competitive Advantage, Information technology, Product Quality